WATER PLANNING IN ALCOBAÇA CISTERCIAN LANDS - Valério Maduro, António; De Mascarenhas, José Manuel; Ferreira jorge, Virgolino (Riparia, 2017)
Abstract in English language This paper concerns the main domain (“coutos”) of the Cistercian Abbey of Alcobaça (central Portugal), founded in 1153. It shows the involvement of the monks in shaping hydraulic landscapes along time. This monastic territory is limited westwards by the Atlantic ocean with a cliff coast indented by two large gulfs, the former Pederneira and Alfeizerão lagoons, sanded up presently. These landscapes have been consolidated along with the monks’ intervention in the hydrographic plan, particularly through a network of canals, the types of which can be summarized as follows: - canals for water conveyance and evacuation, to and from the abbey buildings; - canals related with water-powered engines as grain-, oil-, saw- and fulling-mills, forges and other industrial devices; - canals consequent to the diversion of rivers and streams with two main purposes: . to drain the fields in order to improve the marshes for agricultural use; . to irrigate cultures. Keywords: Hydraulic landscapes, Canals, Cistercians, Alcobaça Abbey. Abstract in Portuguese language Este artigo respeita os coutos da Abadia Cisterciense de Alcobaça (Portugal Central), fundada em 1153. Nele se apresenta o envolvimento dos monges na modelação de paisagens hidráulicas ao longo do tempo. Este território monástico está limitado pelo Oceano Atlântico, a Oeste, sendo a costa escarpada recortada por dois grandes golfos, as antigas lagoas de Pederneira e de Alfeizerão, actualmente assoreadas. A intervenção dos monges permitiu que estas paisagens se fossem consolidando, através sobretudo da instalação de uma rede de canais cuja tipologia pode ser resumida do seguinte modo: - canais para adução aos edifícios abaciais e para evacuação da água destes; - canais para a produção da energia hídrica necessária a moinhos, lagares, serrações, pisões, forjas e outros equipamentos industriais; - canais relacionados com o desvio de rios e ribeiros, com duas finalidades básicas: - drenagem dos campos com vista à sua recuperação para a agricultura; . irrigação agrícola. Palavras- Chave: Paisagens hidráulicas, Canais, Cistercienses, Abadia de Alcobaça